2014
DOI: 10.1038/srep03821
|View full text |Cite
|
Sign up to set email alerts
|

Layered SiC Sheets: A Potential Catalyst for Oxygen Reduction Reaction

Abstract: The large-scale practical application of fuel cells cannot come true if the high-priced Pt-based electrocatalysts for oxygen reduction reaction (ORR) cannot be replaced by other efficient, low-cost, and stable electrodes. Here, based on density functional theory (DFT), we exploited the potentials of layered SiC sheets as a novel catalyst for ORR. From our DFT results, it can be predicted that layered SiC sheets exhibit excellent ORR catalytic activity without CO poisoning, while the CO poisoning is the major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 64 publications
1
61
1
Order By: Relevance
“…The current lost of Pt/C is predominantly caused by the blockage of active sites on Pt nanoparticles by absorbing CO or methanol oxidation intermediate products [27,29]. It is reported that the adsorption energy (1.86 eV) of CO on Pt (111) surfaces is twice as large as that of O 2 (0.84 eV) [30]. These results reveal that the N-self-doped carbon catalyst has a significantly superior stability and immunity towards methanol crossover and CO poisoning than that of Pt/C, indicating a promising alternative to Pt-based catalyst for alkaline fuel cell at cathode.…”
Section: Resultsmentioning
confidence: 98%
“…The current lost of Pt/C is predominantly caused by the blockage of active sites on Pt nanoparticles by absorbing CO or methanol oxidation intermediate products [27,29]. It is reported that the adsorption energy (1.86 eV) of CO on Pt (111) surfaces is twice as large as that of O 2 (0.84 eV) [30]. These results reveal that the N-self-doped carbon catalyst has a significantly superior stability and immunity towards methanol crossover and CO poisoning than that of Pt/C, indicating a promising alternative to Pt-based catalyst for alkaline fuel cell at cathode.…”
Section: Resultsmentioning
confidence: 98%
“…Notably, Jiang et al have recently suggested that the layered SiC sheets are shown to be energetically favorable than cubic ones when the layer number is less than 4 [50]. To avoid the interaction of layered SiC sheet and its periodic image, we set the modulus unit cell vector in the z direction to be as large as 15Å according to test as shown in Table S3.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The most interesting is that graphene-like SiC sheet can provide more active reaction sites than present doped carbon materials. For example, layered SiC sheets can serve as a feasible metal-free oxygen reduction reaction electrocatalyst [50]. Since layered SiC sheet possess high chemical reactivity, we highly wonder whether it can be used as a potential candidate as the metal-free catalyst for NO reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some two-dimensional layer-like oxygen reduction reaction (ORR) catalysts such as N-doped single-layer graphene [47], B and N co-doped graphite layers [48], transition metal di-chalcogenides (MoSe 2 , WS 2 , WSe 2 ) [49], iron polyphthalocyanine [50] and Co 0.85 Se/graphene hybrid nanosheets [51] have been widely investigated in the past five years. Even the layered SiC sheets have also been calculated to be a potential effective catalysts for ORR based on the density functional theory [52]. Thus, it is of great interest to develop and investigate the characteristics and electrochemical performance of two-dimensional Li 3 VO 4 nanostuctures as well as their hybrids with graphene sheets.…”
Section: Accepted Manuscriptmentioning
confidence: 99%